The power of social interactions as a tool to influence the development of creativity among professional groups in coworking spaces in Prague - Shut, Lizaveta (2023)
The thesis investigates the impact of social interactions in coworking places in Prague and how it influences creativity among creative IT professionals. The main objective is to explore coworking spaces' essential methods to boost creativity among professional groups and their connection with soft skills development. The literature review part describes the recent studies related to the topic. The practical part of the thesis uses the mixed research method that includes collecting data through online questionnaires and conducting semi-structured interviews with members and community managers of coworking places in Prague. The methodology part provides a detailed description of the selected methods, sampling characteristics and data analysis methods. The research findings provide relevant arguments about the impact of creativity on social interactions in coworking spaces.